ANALISIS PENGARUH BENTUK DINDING GESER BETON BERTULANG TERHADAP KAPASITAS DAN LUAS TULANGAN - Wiryadi, I Gede Gegiranang; Sudarsana, I Ketut (JURNAL SPEKTRAN; Vol 7 No 2 (2019): Vol. 7 No. 2, JULI 2019, 2019)
ANALYSIS OF SHAPE EFFECT OF REINFORCED CONCRETE SHEAR WALL DUE TO CAPACITY AND REBAR AREA ABSTRACT There are several way to improve the structural performance of high rise building in anticipate horizontal drift and reduce structure time period, one of the solution is by adding the shear wall. Shear wall has many type if it divided by it’s shape, including I-Shape, L-Shape, T-Shape and IWF-Shape that can be adapted with the available plan and building shape. The shape difference of shear wall is linear with the difference of shear wall capacity in enduring the forces and the difference of rebar area. By using S-concrete version 7.02 when modelling 4 type of shear walls that given the same axial force and moment and the same materials, it can be concluded that the biggest axial forces and moment capacity is on the I-Shape shear wall as evidenced by axial: momen ratio compare to the capacity as big as 0.71, followed by IWF-Shape (0.86), and L-Shape and T-Shape (both 0.96). Evaluated from total of rebar area, starting from the smallest, I-Shape shear wall with area 29166 mm2, followed by L-Shape (36666 mm2), T-Shape (40833 mm2), and IWF-Shape (51250 mm2).